The Dynamics of Operating Income in the Norwegian Banking Sector - Henrik Andersen; Sigbjørn Atle Berg; Eilev S. Jansen (Norges Bank, 2008)
The banking literature contains only a handful of studies of how bank revenues vary over the business cycle, and nearly all of these studies look exclusively on the net interest margin. The general conclusion has been that the margin tends to increase during recessions and decrease during booms. In this paper we study the effect of macroeconomic variables on the operating income in the Norwegian banking sector. We contribute to the existing literature by looking at how net interest income as well as fee income varies over the cycle in an error correction framework, which allows us to identify both short term and long term relationships. Our paper also differs from most previous studies by taking into account the volume effect as well as the price effect of the business cycle.
hdl:11250/2497772
Keywords: G21; E32; 330; bank operating income; business cycles